The atlas of atlases exploring the most important atlases in history and the cartographers who made them - Parker, Philip 1965- (The Ivy Press, 2022)
Atlases are books that changed the course of history. Pored over by rulers, explorers and adventures these books were used to build empires, wage wars, encourage diplomacy and nurture trade. Written by Philip Parker, an authority on the history of maps, this book brings these fascinating artefacts to life, offering a unique, lavishly illustrated guide to the history of these incredible books and the cartographers behind them. This beautiful book will engross readers with its detailed, visually stunning illustrations and fascinating story of how map-making has developed throughout human history. --
Keywords: Geschichte 1200-2022; World atlases / world maps; Antiques & collectables: pictures, prints & maps; REFERENCE / Atlases, Gazetteers & Maps; HISTORY / Historical Geography; Atlases - History; Atlas; Kartografie